Development of a TaqMan-based real-time PCR assay for detection and quantification of Pythium aphanidermatum in plant and soil samples. Issue 4 (1st October 2020) - Yu, Jia; Xu, Heng; Lu, Xinyu; Tian, Yuee; Peng, Hao; Shen, Danyu; Dou, Daolong
ABSTRACT: The soilborne oomycete pathogen Pythium aphanidermatum causes damping-off and root rot in a wide range of economically important crops and vegetables. Effective P . aphanidermatum disease management is hindered by the lack of accurate pathogen detection methods. We developed a TaqMan-based real-time PCR tool for efficient detection and quantification of P . aphanidermatum presence in plant and soil samples. Eukaryotic peptide chain release factor subunit 1 ( eRF1 ) was selected as the marker gene based on bioinformatic analysis. P . aphanidermatum DNA was quantified by using a eRF1 -containing plasmid as the reference standard. This approach is sensitive enough to detect as low as 10 fg of P . aphanidermatum genomic DNA or 10 copies of reference plasmid. In a specificity evaluation, eight P . aphanidermatum isolates can be precisely detected out of 44 plant pathogen isolates. Moreover, P . aphanidermatum DNA can be detected in plant leaves 10 min after inoculation when there is no symptom appearance at all. Meanwhile, this assay successfully detected P . aphanidermatum zoospores in the soil at the sensitivity level of 100 zoospores/g, a density sufficient for inhibiting seedling growth. Taken together, the real-time PCR tool could be valuable for the early surveillance and quantification of P . aphanidermatum spread in the field.